The Development of The Indonesian Taxation System amid a Fiscal Crisis (an Analysis of Abu Yusuf's Thought) - Feni Apriliyani; Muhamad Muztahidin; Wartoyo wartoyo (Sekolah Tinggi Agama Islam Kuningan, 2025)
Low levels of tax compliance, inequality in tax contributions, and suboptimal tax management, particularly in the informal sector and the digital economy, pose significant challenges to the Indonesian tax system amid the fiscal crisis. This study aims to analyze Abu Yusuf's thoughts on developing the Indonesian tax system, particularly in addressing problems during the fiscal crisis. This study employs a qualitative approach, utilizing a literature review method, to examine Abu Yusuf's thoughts as presented in the Book of al-Kharaj, as well as other literature that discusses the implementation of the tax system in Indonesia. The results of the study indicate that the principle of justice in tax collection, as put forward by Abu Yusuf, such as progressive taxes adjusted to the community's ability and transparency in tax management, are relevant to be applied in the Indonesian tax system. Therefore, it is recommended that the Indonesian government introduce a more progressive tax policy that prioritizes the informal sector, increases transparency, and enhances the digitalization of the tax system to create a fairer and more efficient tax system. In the context of the ongoing fiscal crisis, implementing a more progressive tax policy that includes the informal sector, supported by digitalization of the tax system, can broaden the tax base while increasing taxpayer compliance.